Peranan Etika Profesi Pendidik dalam Membangun Nilai-nilai Karakter Mahasiswa Pendidikan Guru Pendidikan Anak Usia Dini - Pangaribuan, Tumewa; Harianja, Sri Indriani; Vidri, Nabila; Saniati, Sofi; Aszari, Siti Annisa (Universitas Batanghari Jambi, 2025)
This research aims to show that character values are very necessary for preparing students to become teachers with good character. This research uses a literature study method with data collection techniques, researchers collect journals and other relevant sources related to the role of professional ethics for educators in student life. Educator professional ethics lectures in building the character values of teacher education and early childhood education students are very important, as prospective teachers must be able to become role models for the school and environment in the future.